Converting scores between the PANSS and SAPS/SANS beyond the positive/negative dichotomy. (November 2021) - Grot, Stéphanie; Giguère, Charles–Édouard; Smine, Salima; Mongeau-Pérusse, Violaine; Nguyen, Dana Diem; Preda, Adrian; Potvin, Stéphane; van Erp, Theo G.M.; FBIRN,; Orban, Pierre
Highlights: Factor analysis identified symptom dimensions common to both the PANSS and SAPS/SANS. Symptom dimensions have good face validity in both the positive and negative domains. Between-scale conversions have good to excellent reliability for 5 out of 6 symptom dimensions. Conversion equations are implemented in an r shiny app to facilitate their use by the community. Abstract: Previous work provided conversion equations for overall indices of positive and negative symptomatology between the Positive and Negative Syndrome Scale (PANSS) and the Scales for the Assessment of Positive/Negative Symptoms (SAPS/SANS). Our objective was to provide such conversion equations for subdomains of positive and negative symptomatology in order to better account for the diversity of symptom profiles in schizophrenia. Symptoms severity was assessed using both the PANSS and SAPS/SANS in 205 patients with schizophrenia. Two exploratory factor analyses combining items from both scales were first performed separately in the positive and negative symptom domains. Positive factors were termed 'Hallucinations', 'Delusions' and 'Disorganization', while negative factors were associated with 'Expressivity', 'Amotivation' and 'Cognition', consistent with current descriptions of symptom dimensions in schizophrenia. For each factor, linear regression analyses were conducted on 80% of the data to obtain conversion equations from the PANSS to the SAPS/SANS and vice versa. Reliability was then evaluated on the 20% remaining data, with good to excellent intra-class correlation coefficients between the original and predicted scores for all but the cognition factor. These findings show that symptom severity scores can be converted with good accuracy between clinical scales beyond the positive/negative symptom dichotomy.